Validation of a Novel Method for Determining the Renal Threshold for Glucose Excretion in Untreated and Canagliflozin-treated Subjects With Type 2 Diabetes Mellitus - Polidori, David; Sha, Sue; Ghosh, Atalanta; Plum-Mörschel, Leona; Heise, Tim; Rothenberg, Paul (The journal of clinical endocrinology and metabolism, 2013)
Context:The stepwise hyperglycemic clamp procedure (SHCP) is the gold standard for measuring the renal threshold for glucose excretion (RTG), but its use is limited to small studies in specialized laboratories.Objective:The objective of the study was to validate a new method for determining RTG using data obtained during a mixed-meal tolerance test (MMTT) in untreated and canagliflozin-treated subjects with type 2 diabetes mellitus (T2DM).Design:This was an open-label study with 2 sequential parts.Setting:The study was performed at a single center in Germany.Patients:Twenty-eight subjects with T2DM were studied.Interventions:No treatment intervention was given in part 1. In part 2, subjects were treated with canagliflozin 100 mg/d for 8 days. In each part, subjects underwent an MMTT and a 5-step SHCP on consecutive days.Main Outcome Measures:For both methods, RTG was estimated using measured blood glucose (BG) and urinary glucose excretion (UGE); estimated glomerular filtration rates were also used to determine RTG during the MMTT. The methods were compared using the concordance correlation coefficient and geometric mean ratios.Results:In untreated and canagliflozin-treated subjects, the relationship between UGE rate and BG was well described by a threshold relationship. Good agreement was obtained between the MMTT-based and SHCP-derived RTG values. The concordance correlation coefficient (for all subjects) was 0.94; geometric mean ratios (90% confidence intervals) for RTG values (MMTT/SHCP) were 0.93 (0.89–0.96) in untreated subjects and 1.03 (0.78–1.37) in canagliflozin-treated subjects. Study procedures and treatments were generally well tolerated in untreated and canagliflozin-treated subjects.Conclusions:In both untreated and canagliflozin-treated subjects with T2DM, RTG can be accurately estimated from measured BG, UGE, and estimated glomerular filtration rates using an MMTT-based method.